Społeczno-kulturowa specyfika przygranicznych miast podwójnych Europy jako problem badawczy - Szalbot, Magdalena (Studia Etnologiczne i Antropologiczne, 2011)
The centres, located in Europe, through which the borderline of two countries goes are marked by socio-cultural separateness worth documentation and complex examination. Ethnology, in line with other disciplines, should get engaged in the analysis of phenomena and socio-cultural processes revealing themselves in borderline double towns. The towns divided by the national border have not constituted a frequent type of town. There are several dozen towns divided by a national border in Europe. Borderline “two-towns” are peculiar “cultural laboratories” in which it is possible to observe interesting trans-border phenomena every day. The majority of European double towns are distinguished by biculturalism, bilingualism, and bicurrency until recently. Crossing the border means encountering different architecture, traditions and life style of the community members who experience other problems publicized by different media on both border sides. Political, system and economic Changes happening on a macro scale on the one side and sometimes on both sides of the border in borderline “double towns” evoke extremely dynamic and diversified socio-cultural processes. Borderline double town relations spoil every-day cultural “clashes”, revealing their own complexes and those belonging to their neighbours, as well as reluctance to maintain rather forced than spontaneously-formed kind neigbourhood relations. A counterbalance of negative phenomena typical of many double towns constitutes planned enterprises having a positive influence on the development of borderline towns: positive results of the activisation of local trade, accelerated”course of tolerance” which the citizens of such towns participated in, initiated processes of transforming borderline towns in towns of borderland, and taking on the function of borderline centres and capitals of Euroregions. An important stage in improving the relations between the inhabitants of both parts of borderline towns is moving from the institutionalized cooperation to informal one.